Perianesthetic management in a teenager with focal cortical dysplasia who underwent an epilepsy surgery - Yeap, Boon Tat; Koo, Thai Hau; Ang, Song Yee; Hassan, Mohamad Hasyizan (Faculty of Medicine Universitas Indonesia, 2025)
Medically resistant epilepsy (MRE) is defined as the failure of adequate trials of 2 tolerated and appropriately used antiepileptic drugs to achieve sustained seizure freedom, where epilepsy surgery (ES) is indicated in patients with MRE due to complex epileptic syndromes, such as Lennox-Gastaut and Sturge-Weber syndromes, and focal cortical dysplasia (FCD), to disconnect the epileptogenic foci from other cerebral structures. ES demands excruciating perianesthetic considerations due to its complexity and various pharmacological interactions. Our patient is a 15-year-old male with MRE secondary to FCD. He successfully underwent ES in our neurosurgical center. We describe our perianesthetic challenges in addition to a brief overview of MRE and FCD.